Effectiveness of interactive PowerPoint media integrated with augmented reality in improving student learning outcomes on the Solar System topic - Dede Alfianto; Ratna Wahyu Wulandari; Ummiy Fauziyah Laili; Mochammad Desta Pradana (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
Conventional learning methods that lack interactivity often make it difficult for students to understand concepts, resulting in low learning outcomes. This study aims to determine the feasibility and effectiveness of interactive PowerPoint learning media integrated with Augmented Reality (AR) in improving students' learning outcomes on the topic of the solar system. The research design used is a one-group pretest-posttest design. Media feasibility was assessed through expert validation by design, material, and media experts, as well as a small group trial. The validation results showed that the media was highly feasible, with an average feasibility score of 98% from the three experts, along with positive responses from the small group trial. The effectiveness of the media was analyzed using normality tests, homogeneity tests, paired sample t-tests, and N-Gain calculations. The t-test results showed a significant value of 0.000 < 0.05, indicating a significant difference between pre-test and post-test scores. The average N-Gain score of 0.60 or 60.21% falls into the moderate and fairly effective category. Therefore, the media is considered highly feasible and fairly effective for use in science learning at the junior high school level.